Periodontal Implications of Orthodontic Treatment: Assessment of The Balance between Tooth Movement and Surrounding Tissue - Haleem, Riyam; Noor Musa; Ghufran M. Hayder; Hasanain sabeeh (Indonesian Journal on Health Science and Medicine, 2025)
Orthodontic treatment also aims to maintain ideal periodontal health. Gingival/periodontal conditions and orthodontic interventions have a complicated relationship because orthodontic forces invariably affect periodontal structures. The aims of this study were to investigate the plaque, and gingival index, before and during orthodontic treatment. In order to fully evaluate the periodontal health of orthodontic patients, a study spanning six months was carried out of 100 adult permanent dentition subjects were included in the sample. Participants were recruited from a specialized orthodontic clinic, and OPI, and OGI were assessed at multiple time points: baseline, 3 months, and 6 months post-treatment initiation. The study found that there were significant increasing in orthodontic plaque index, and orthodontic gingival index before orthodontic appliance insertion and over 6 months of post treatment. This study highlights the significant impact of orthodontic appliances on both gingival health and plaque accumulation. The increase in the Orthodontic Gingival Index and Orthodontic Plaque Index during treatment emphasizes the need for effective oral hygiene strategies for patients undergoing orthodontic therapy. Future research should focus on developing innovative methods to help orthodontic patients improve their oral hygiene practices and prevent gingival inflammation and plaque accumulation. Highlights: Orthodontic treatment led to significant increases in gingival inflammation and plaque accumulation over six months. Both Orthodontic Gingival Index (OGI) and Orthodontic Plaque Index (OPI) showed steady rises from baseline to 6 months. Findings emphasize the need for strict oral hygiene strategies during orthodontic therapy to prevent periodontal complications.